Pemanfaatan Kemajuan Teknologi Dan Motivasi Dalam Kegiatan Pembelajaran Di Sekolah Guna Meningkatkan Profesionalisme Guru (International Forum of Researchers and Lecturers, 2023)
A teacher is an educator whose professionalism is really needed in education in order to improve the quality of education and Human Resources (HR). The professionalism of teachers has a huge impact on the results of the teaching provided in schools through technology and motivation which will later become the key to realizing students' dreams in the future. Therefore, it is better for every school to have professional teachers or teaching staff so that the world of education in Indonesia becomes more advanced and develops even better in the future. The aim of preparing this article is to discover the influence of teacher professionalism on the progress and development of technology and student motivation in the learning process at school. The aim of preparing this article is to find the influence of teacher professionalism on the progress and development of technology and student motivation in learning activities at school. This research uses a library study method. The research results show that teachers or professional teaching staff have a big influence on students' knowledge regarding technological progress and development and also the motivation provided has an impact on students' learning activities at school.